Female Imagery in Bogomil Myth, Exegesis and Social Reality: An Overview. (2nd January 2022) - Radovanović, Bojana
ABSTRACT: This paper will examine the role of women and, more broadly, the female imagery presented in Bogomil doctrine and practice, as reflected in the Bogomil myth, Biblical exegesis and social reality. The paper explores the relationship between the Bogomil mythological accounts and exegetical practice on the one hand, and the society on the other, in order to clarify whether these Bogomil literary techniques were disconnected from society, or not, and to what extent. Bogomil exegesis mirrored the underlying situational contexts, or vice versa. This analysis will also contribute to the wider topic of re-assessing the Bogomil religious identity, as shaped by the elements of the apostolic Christian tradition, but also by extra-canonical and heterodox textual strands.